Efeitos não-inerciais em Anéis Quânticos - Dantas, Lincoanderson Oliveira (2015)
In this thesis, we investigate by the first time the impact of non-inertial effects associated with the rotation of the reference system on charged and neutral particles confined by a quantum ring, which is described by the potential of Tan-Inkson. The contribution of the rotation is introduced by its coupling with angular momentum of the system. We show that the rotation is introduced via a non-minimum coupling to the kinetic part of the Hamiltonian describing the quantum dynamics of systems studied here. Thus, we show that non-inertial effects of the rotation induce on the quantum properties of the particles similar effects generated by a magnetic field. We also investigated the contribution of a screw dislocation on the physical properties of the particles. The topological defect contributes as a torsion source, presenting a contribution similar to the Aharonov-Bohm flux. Besides charged particles (electrons and holes), we also study the effects of rotation on neutral particles in three different scenarios: a neutral particle with a permanent magnetic dipole moment coupled by the Aharanov-Casher interaction; a neutral particle with a permanent electric dipole moment coupled by the interaction proposed by He-McKellar-Wilkens and a neutral particle with an electric dipole moment induced by the field configuration proposed by Wei-Han-Wei. In all three cases it is shown the similarity between the neutral and charged particles. We analyze the non-relativistic quantum dynamics of these particles by solving the Schrödinger equation. In addition to the energy spectrum and wave functions, we calculate the persistent current and the magnetization for the four systems studied here, and we also analyzed, from the expression for the persistent current for quantum rings, the limit case for quantum dots.